2016
DOI: 10.14411/fp.2016.024
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and intensity of Streblidae in bats from a Neotropical savanna region in Brazil

Abstract: Bats of the family Phyllostomidae are common hosts to streblids known as bat flies. Here, we discuss the component community, prevalence and intensity of infection with species of Streblidae on an assemblage of phyllostomid bats in the Cafuringa Environmental Protection Area (APA Cafuringa) in the core area of the Cerrado in Central Brazil. A total of 1 841 streblid individuals of 24 species occurred on 752 bats of 14 species. Ten species of streblids infected Glossophaga soricina (Pallas), whereas seven or fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
2
8
1
2
Order By: Relevance
“…Concerning the richness bat flies species, this study reported lower records when compared to similar studies from other Cerrado ecoregions in Brazil (Eriksson et al 2011, Santos et al 2013, Vasconcelos et al 2016, Aguiar and Antonini 2016, Barbier and Graciolli 2016. However, like Graciolli and Aguiar (2002), a higher richness of bat species with lower sampling effort was recorded.…”
Section: Discussioncontrasting
confidence: 72%
“…Concerning the richness bat flies species, this study reported lower records when compared to similar studies from other Cerrado ecoregions in Brazil (Eriksson et al 2011, Santos et al 2013, Vasconcelos et al 2016, Aguiar and Antonini 2016, Barbier and Graciolli 2016. However, like Graciolli and Aguiar (2002), a higher richness of bat species with lower sampling effort was recorded.…”
Section: Discussioncontrasting
confidence: 72%
“…In D. rotundus , association patterns were similar to those previously reported, with S. wiedemanni and T. parasiticus representing the most common ectoparasites on this bat (Hofstede et al . , Aguiar & Antonini ). However, the response of these two species of Streblidae to habitat fragmentation was contrary with the predictions.…”
Section: Discussionmentioning
confidence: 96%
“…A associação entre Carollia perspicillata e T. joblingi é recorrente em diversos estudos realizados no Cerrado (Graciolli et al, 2006a, b;Eriksson et al, 2011;Santos et al, 2013;Vasconcelos et al, 2016;Barbier & Graciolli, 2016, Dornelles et al 2017Graciolli et al 2017). Os estudos realizados no Cerrado não apresentam um padrão definido quanto aos valores de infestação dessa relação, com prevalência variando de 40,5% (Erikson et al 2011) a 91% (Aguiar & Antonini, 2016) e intensidade média de infestação variando de 2,3 (Santos et al, 2013) a 3,5 (Barbier & Graciolli, 2016). Entretanto, os poucos estudos que descrevem os índices de parasitismo nessas regiões (Erikson et al, 2011;Santos et al, 2013;Vasconcelos et al, 2016;Aguiar & Antonini, 2016;Barbier & Graciolli, 2016;Dornelles et al, 2017) demonstraram uma tendência a infestações mais intensas em populações de C. perspicillata com maiores prevalências de parasitismo.…”
Section: Discussionunclassified
“…Poucos estudos avaliam as associações entre moscas e morcegos em regiões de Cerrado utilizando índices parasitológicos como a prevalência, intensidade de infestação em uma espécie de hospedeiro ou mesmo a especificidade entre as associações (e.g. Aguiar & Antonini, 2011;Eriksson et al, 2011;Urbieta et al, 2014;Vasconcelos et al, 2016;Aguiar & Antonini, 2016;Barbier & Graciolli, 2016;Dornelles et al, 2017). Esses parâmetros preenchem lacunas sobre a ecologia do parasitismo, e podem ser aplicados para avaliar fatores que influenciam nas associações, como o clima (Lourenço & Palmerim, 2007) ou os aspectos reprodutivos dos hospedeiros (Bertola et al, 2005).…”
unclassified